2006
DOI: 10.1074/jbc.m512015200
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis YkuV Is a Thiol:Disulfide Oxidoreductase Revealed by Its Redox Structures and Activity

Abstract: The Bacillus subtilis YkuV responds to environmental oxidative stress and plays an important role for the bacteria to adapt to the environment. Bioinformatic analysis suggests that YkuV is a homolog of membrane-anchored proteins and belongs to the thioredoxin-like protein superfamily containing the typical Cys-Xaa-XaaCys active motif. However, the biological function of this protein remains unknown thus far. In order to elucidate the biological function, we have determined the solution structures of both the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…In support of this sequence analysis, studies by Zhang et al demonstrated that AhpT becomes oxidized upon interaction with oxidized AhpA in vitro, suggesting that AhpT can reduce AhpA (52). Additionally, B. subtilis thioredoxin reductase (trxB) can reduce the oxidized form of AhpT in vitro (52).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In support of this sequence analysis, studies by Zhang et al demonstrated that AhpT becomes oxidized upon interaction with oxidized AhpA in vitro, suggesting that AhpT can reduce AhpA (52). Additionally, B. subtilis thioredoxin reductase (trxB) can reduce the oxidized form of AhpT in vitro (52).…”
Section: Resultsmentioning
confidence: 78%
“…Sequence and structural analysis of AhpT clearly classifies AhpT as a CXXCcontaining, thioredoxin-like protein; compared to other thioredoxin family proteins, the sequence of AhpT clusters with the sequences of other thioredoxins from B. subtilis (Fig. 1C) (52). However, AhpT is a unique thioredoxin; it most resembles the membrane-anchored thioredoxin-like protein ResA that is important for cytochrome c biosynthesis (53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EvoI2 contains, apart from an SNP in tagE, SNPs in ykuV and yusQ. The function of yusQ is unknown, but ykuV encodes a hypothetical thiol:disulfide oxidoreductase, involved in protection of proteins against oxidative damage (Zhang et al, 2006).…”
Section: Whole-genome Sequencingmentioning
confidence: 99%
“…HADDOCK comprises a series of Python scripts that run on top of the structure determination programs ARIA (22) and CNS (23); it is designed to use biochemical and/or biophysical interaction data to generate AIRs and to then carry out docking calculations to generate models of a complex that satisfy the experimental data (37)(38)(39).…”
Section: The Dna-binding Properties Of Myt1 Znf Combinations-mentioning
confidence: 99%